Chitosan and Aloe vera gel formulations as wound healing agents in episiotomy (Research, Society and Development, 2021)
Episiotomy is an obstetric technique that consists of making an incision in the perineum during vaginal childbirth, to facilitate the baby to pass through. After delivery, the perineal region is sutured with absorbable threads to heal the cut. However, are frequent reports of pain, infections, and dyspareunia after the execution of this technique. In this context, the use of biomaterials becomes relevant as they promote faster and safer tissue repair, making it an attractive alternative for the healing process of episiotomy. Based on the physical-chemical and biological properties of chitosan and Aloe vera, this research developed three different vaginal gels, with the purpose of promoting tissue regeneration and infection prevention post-episiotomy. Chitosan solutions with concentrations of 5% w/v were prepared by dissolving the chitosan powder in 2% v/v aqueous solution of acetic acid. After the extraction and processing of the mucilage, the pulp of the Aloe vera leaf was added to the chitosan gel in the proportions of 1, 2, and 3% v/v. All formulations were neutralized by the slow drip technique of a neutralizing solution of sodium hydroxide (2 M). The compositions were analyzed according to their organoleptic aspect, optical microscopy, spreadability, hydrogen potential, absorption spectroscopy, cytotoxicity, and rheological behavior. Based on the results obtained, it was possible to conclude that gels produced have the potential to be used as vaginal gels.